О соотношении «частей речи» и «падежей» в русском языке(On the Interrelations Between “Parts of Speech” and “Cases” in Russian) - Lönngren, Lennart (Poljarnyj vestnik, 2002)
The seemingly simple relations between these two categories turn out to be quite complex in the framework of a dependency grammar in which all kinds of segmental linguistic signs are involved: not only free, explicit words but also morphologically incorporated lexemes and implicit lex- emes. To the set of traditional cases are added CAS (general case), AGR (agreement case), PRP (prepositional phrase), CJP (conjunction phrase), and NOC ("no case", not marked for case). The part of speech category is enriched by the introduction of two subword labels, AFF (derivational affixes) and FLEX (desinencies). The possible combina- tions of the "part of speech" and "case" labels are investigated separately for each type of lexeme.
Keywords: Russian; language; case; part of speech